Pengaruh Return On Equity Dan Net Profit Margin terhadap Harga Saham pada Perusahaan Perkebunan yang Terdaftar di Bursa Efek Indonesia - Muslih Muslih; Yasrin Musthafa Bachri (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2020)
The purpose of this study is to determine the effect of Return On Equity and Net Profit Margin on Share Prices on plantation companies listed on the Indonesia Stock Exchange in 2014-2018. The sample companies are plantation companies listed on the Indonesia Stock Exchange in 2014-2018 and have met the specified criteria. The sample companies obtained were 7 (seven) plantation companies listed on the Indonesia Stock Exchange in 2014-2018. This research uses the technique Multiple Linear Analysis (Miltiple Integration) using Simultaneous Test (F) and Partial Test (t) at Level of Significance 5% (α = 0.005). From the results of Simultaneous Test (F) shows that Return On Equity and Net Profit Margin simultaneously affect the stock price. While the Partial Test (t) shows that Return On Equity has a significant value below 0.05years 0.000. This means that Return On Equity has a significant influence on stock prices. Whereas Net Profit Margin is above 0.05 which is 0.435. From these results it can be seen that partially Net Profit Margin has no effect on stock prices. From the Determination Coefficient test results obtained 50.1% variation of changes in stock prices can be explained by Return On Equity and Net Profit Margin, while the remaining 49.9% is explained by other variables outside the model.